Competencies for Spiritual Care Professionals Specializing in Palliative and Bereavement Care in Canada: A Mixed-Methods Study Using Qualitative Interviews and Modified Delphi Survey. (September 2022) - Stang, Vivian; Barnes, Peter; Enfield, Christine; Koots, Heather
The purpose of this project was to update competencies for spiritual care professionals specializing in palliative and bereavement care in Canada. Phase one feedback was obtained from 11 clients: six inpatients with greater than two weeks of life expectancy using interviews and five bereaved family members in a focus group. Results were analyzed for congruence or discordance with draft competencies. In phase two, 22 spiritual care experts reached a consensus on nine competencies using a modified Delphi survey. Two limitations were the small sample size and cultural and religious homogeneity of participants.